Mycobacteria-Specific T Cells May Be Expanded From Healthy Donors and Are Near Absent in Primary Immunodeficiency Disorders - Patel, Shabnum; Lang, Haili; Sani, Gelina; Freeman, Alexandra F.; Leiding, Jennifer; Hanley, Patrick J.; Cruz, Conrad Russell; Grant, Melanie; Wang, Yunfei; Oshrine, Benjamin; Palmer, Cindy; Holland, Steven M.; et al. (Frontiers in Immunology, 2019)
Mycobacterial Infections can be severe in patients with T-cell deficiency or phagocyte disorders, and treatment is frequently complicated by antimicrobial resistance. Restoration of T-cell immunity via stem cell transplantation facilitates control of mycobacterial infections, but presence of active infections during transplantation is associated with a higher risk of mortality. Adoptive T cell immunotherapy has been successful in targeting viruses, but has not been attempted to treat mycobacterial infections. We sought to expand and characterize mycobacterial-specific T-cells derived from healthy donors in order to determine suitability for adoptive immunotherapy. Mycobacteria-specific T-cells (MSTs) were generated from 10 healthy donors using a rapid ex vivo expansion protocol targeting five known mycobacterial target proteins (AG85B, PPE68, ESXA, ESXB, and ADK). MSTs were compared to T-cells expanded from the same donors using lysate from M. tuberculosis or purified protein derivative from M. avium (sensitin). MST expansion from 7 patients with primary immunodeficiency disorders (PID) and 2 patients with IFN- autoantibodies and invasive M. avium infections. MSTs expanded from healthy donors recognized a median of 3 of 5 antigens, with production of IFN-, TNF, and GM-CSF in CD4+ T cells. Comparison of donors who received BCG vaccine (n=6) to those who did not (n=4) showed differential responses to PPE68 (p=0.028) and ADK (p=0.015) by IFN- ELISpot. MSTs expanded from lysate or sensitin also recognized multiple mycobacterial antigens, with a statistically significant differences noted only in the response to PPE68 (p=0.016). MSTs expanded from patients with primary immunodeficiency (PID) and invasive mycobacterial infections showed activity against mycobacterial antigens in only 2 of 7 subjects, whereas both patients with IFN- autoantibodies recognized mycobacterial antigens. Thus, MSTs can be generated from donors using a rapid expansion protocol regardless of history of BCG immunization. Most tested PID patients had no detectable T-cell immunity to mycobacteria despite history of infection. MSTs may have clinical utility for adoptive immunotherapy in T-cell deficient patients with invasive mycobacterial infections.